Профессор Николай Егорович Бачериков — известный отечественный психиатр, талантливый представитель санкт-петербургской и харьковской психиатрических школ - Воронцов, М.П.; Петрюк, П.Т.; Петрюк, А.П. (Фізико-хімічний інститут ім. О.В.Богатського НАН України, 2008)
На основі джерел спеціальної літератури, спогадів вчителів, колег і рідних наведено нові дані про життєвий та творчий шлях професора М.Є. Бачерикова – відомого вітчизняного психіатра, вихованця ленінградської психіатричної школи, який своїм науковим здобутком вніс вагомий внесок в розвиток як української психіатричної, так і вищої шкіл. On the basis of sources of the special literature, flashbacks of teachers, colleagues and native new information is resulted about the vital and creative way of the professor M.E. Bacherykov – the known domestic psychiatrist, pupil of Leningrad psychiatric school, which by the scientific achievement brought in ponderable payment in development both Ukrainian psychiatric and high schools.